Impact of growing population in agricultural resource management: exploring the global situation with a micro-level example - Karim, A.H.M Zehadul (2011)
While land use practices often vary greatly across the world, their ultimate purpose usually remains the same for us to having extracted the natural resources for instant societal need, knowing clearly the severe impact of it on environment. A decade ago, David Pimental and his associates (1998) reported to us that that at least ten million hectare of arable land is now being eroded and also abandoned throughout the world every year, and consequently to compensate such loss, a huge amount of replacement is claimed from forest and other sources for agriculture and human settlement. Accordingly, the demographers and environmentalists for that reason have come up with raising issues that main challenge for environmental management throughout the world is to determine our planet’s capacity to sustain such a huge amount of burgeoning human population. The paper thus assesses specifically the impact of growing population on agricultural resource-base around the world creating depressing pressure on sustainable environmental management. To exemplify such a trend of agricultural land use, the paper incorporated a detailed example from an ethnographic case study on indigenous practices and experiences associated with the scientific agricultural knowledge to cope up with and/or adapt to the adverse situation caused by the severe impact of a growing population on agricultural sector in rural Bangladesh. Finally, the paper concludes with a modest caution for the people around the world saying that a prudently managed environment and a judicious use of it for our future survival is fully dependent on having an accurate policy planning to keep the population below optimum level.